Pengamanan Data Kolase Digital Menggunakan Metode Advanced Encryption Standard (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Digital Collage is a technique of creating a work of art by sticking or combining several photos into a single unit. technological developments make everything easy, we can easily send files to each other. With the development of technology, collage art has evolved into the digital realm. However, with the ease of disseminating information, digital collage on the internet is very easy to fake or steal. Digital collage requires a digital security to maintain its authenticity and keep it away from irresponsible people. To resolve the problem, a encrypted system was created. This system will use the Advance Encryption Standard method. The encrypted digital collage will provide extra security because only the owner and recipient of the data can see it. From this test it can be concluded that the AES method can be used to encrypt a digital collage.